Brachydactyly Type A3 Is More Commonly Seen in Children With Short Stature But Does Not Affect Their Height Improvement by Growth Hormone Therapy - Wu, Huahong; Li, Yang; Li, Hui (Frontiers in Endocrinology, 2022)
Introduction To analyze the prevalence of brachydactyly type A3 (BDA3) in children with short stature and the effect on growth hormone (GH) therapy. Methods We analyzed the medical records of pediatric patients from July 2009 to July 2021. We included children with short stature defined as their height standard deviation score (HtSDS) < -2 and normal short height as their HtSDS between -2 and -1. We calculated the prevalence of BDA3 in different groups and compared the differences in children’s characteristics and the therapeutic effect of GH therapy between the BDA3 and no BDA3 groups. Results A total of 752 cases were included. The overall prevalence of BDA3 was 23.1%; with a female predominance (30.8% vs. 16.1%, P < 0.01). BDA3 was more prevalent in the short stature group (27.2%) than in the normal short stature group (16.7%) and growth hormone deficiency group (16.5%). Birth length, birth weight, HtSDS, and mid-parental height of children with BDA3 were lower than those without BDA3, but there were no significant differences. In patients with Turner syndrome and idiopathic short stature, the HtSDS of the BDA3 group was significantly lower than that of the no BDA3 group (P < 0.01). During four years of GH therapy, the HtSDS improvement per year in the BDA3 group were 0.79 ± 0.29, 0.50 ± 0.31, 0.20 ± 0.30, and 0.10 ± 0.22, which were not significantly different from those in the no BDA3 group. At the end of treatment, there were no significant differences in the duration of treatment and total HtSDS improvement between these two groups. Conclusions BDA3 is more commonly seen in children with short stature with a female predominance. BDA3 occurrence is independent of the GH pathway and does not affect the therapeutic effect of GH on short stature children.